Evaluasi Bisnis Proses Rekrutmen dan Seleksi Karyawan PT Sumber Alfaria Trijaya Tbk - Mutiara Salsabiil; Dwi Hurriyati (Jurnal Pengabdian Nasional (JPN) Indonesia, 2024)
This research evaluates and improves the efficiency of the employee recruitment and selection process at PT Sumber Alfaria Trijaya Tbk, a leading retail company. The research focus involves marketing strategies for job vacancies, optimizing selection tests, and implementing information technology. Research methods involve document analysis, interviews, and observation. The results show potential improvements in job vacancy visibility, selection test adjustments, and use of human resource information systems.